A Schumpeterian Growth Model with Heterogenous Firms - Antonio Minniti; Carmelo Pierpaolo Parello; Paul S. Segerstrom (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2008)
A common assumption in the Schumpeterian growth literature is that the innovation size is constant and identical across industries. This is in contrast with the empirical evidence which shows that: (i) the innovation size is far from being identical across industries; a (ii) the size distribution of profit returns from innovation is highly skewed toward the low value side, with a long tail on the high value side. In the present paper, we develop a Schumpeterian growth model that is consistent with this evidence. In particular, we assume that when a firm innovates, the size of its quality improvement is the result of a random draw from a Pareto distribution. This enables us to extend the class of quality-ladder growth models to encompass firm heterogeneity. We study the policy implications of this new set-up numerically and find that it is optimal to heavily subsidize R&D for plausible parameter values. Although it is optimal to tax R&D for some parameter values,this case only occurs when the steady-state rate of economic growth is very low.
Keywords: 330